Pengalaman Mahasiswa BKPI UIN Salatiga dalam Menjaga Ketepatan Waktu Shalat Lima Waktu di Tengah Intensitas Bermain Game Online - Deta Anissa Alfiyani; Arrina Fauzia; Rara Larasati (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study aims to explore the experiences of students of the Islamic Educational Guidance and Counseling Program (BKPI) at UIN Salatiga in maintaining the punctuality of the five daily prayers amid the intensity of online gaming activities. This research employed a qualitative approach with a descriptive research design. The participants consisted of six students who actively played online games. Data were collected through in-depth interviews, observations, and documentation, and were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings revealed that the intensity of online gaming influenced the punctuality of prayer performance, particularly for the Asr, Isha, and Fajr prayers. The main factors contributing to delayed prayers were excessive concentration on gameplay, reluctance to leave ongoing matches, and sleep disturbances caused by late-night gaming habits. Nevertheless, the participants demonstrated a strong sense of religious awareness, reflected in feelings of guilt after delaying prayers and efforts to improve their worship practices. The study also found that self-regulation and time management played significant roles in helping students balance online gaming activities and religious obligations. The stronger the students’ self-regulation skills, the greater their ability to maintain prayer punctuality in the midst of rapid digital technological development.